Preparation and characterization of lithium and sodium doped polymethyl methacrylate based gel polymer electrolytes for battery applications / Lisani Othman - Lisani, Othman (2016)
In the present study, two systems of gel polymer electrolyte (GPE) samples composed of poly(methyl methacrylate) (PMMA) as a host polymer dissolved in a binary mixture of ethylene carbonate (EC) and propylene carbonate (PC) organic plasticizing solvents complexed with lithium triflate (LiCF3SO3) and sodium triflate (NaCF3SO3) as doping salts have been prepared by solution casting technique. These systems are the (PMMA– EC – PC – LiCF3SO3) system and the (PMMA – EC – PC – NaCF3SO3) system. The PMMA sample and the unsalted GPE sample (PMMA – EC – PC) have been prepared as a reference. The conductivity of the samples from each system is characterized by impedance spectroscopy. The room temperature conductivity for the highest conducting sample in the PMMA– EC – PC – LiCF3SO3 and PMMA – EC – PC – NaCF3SO3 systems is (2.56 ± 0.41) × 10-3 S cm-1 and (3.10 ± 0.63) × 10-3 S cm-1 respectively. The temperature dependence of conductivity for the GPE samples in both systems from 303 K to 373 K obeys the Arrhenius rule. The activation energy, Ea values have been calculated to be 0.19 eV and 0.18 eV for the highest conducting sample containing lithium salt and sodium salt respectively. The ionic and cationic transference numbers have been evaluated by DC and combined AC and DC polarization techniques to determine the charge carrier species within the GPE samples. Linear sweep voltammetry (LSV) and Cyclic Voltammetry (CV) techniques are performed in order to evaluate the electrochemical stability and properties of the prepared GPE samples. The highest conducting sample from PMMA – EC – PC - LiCF3SO3 and PMMA – EC – PC - NaCF3SO3 systems is found to be electrochemically stable up to 3.3 V and 3.4 V respectively. Fourier Transform Infrared (FTIR) and Raman spectra studies have proven that the salts, LiCF3SO3 and NaCF3SO3 along with plasticizing solvents EC and PC have formed complexes with the PMMA polymer. X-ray diffraction (XRD) reveals that the sample with the highest conductivityvalue at room temperature from each system has an amorphous phase. Field Emission Scanning Electron Microscopy (FESEM) study shows the morphology of these samples. Thermal studies indicate that the PMMA-based polymer electrolytes are stable up to 150 °C and from the glass transition temperature, Tg studies, the enhancement of amorphous region is confirmed. The performance of the cell fabricated employing the highest conducting sample from each system is examined. The cell that has been assembled using the configuration Li |GPE| LiMn2O4 for the GPE sample containing LiCF3SO3 salt and Na |GPE| MnO2 for the GPE sample containing NaCF3SO3 salt exhibits the first discharge capacity of 117 mAh g-1 and 162 mAh g-1 respectively.